Perlindungan Hak Cipta Atas Karya Yang Dihasilkan Dengan Bantuan Artificial Intelligence di Indonesia - Elizabeth Tania; Gunardi Lie (UM.Tapanuli Selatan, 2025)
Limitations on copyright protection can be granted to humans as creators when Artificial Intelligence also plays a role. The research method of this article uses descriptive qualitative research with a document study approach, consisting of legislation, scientific articles, expert legal opinions. The approach used to examine the issue is normative-conceptual in nature, making it more appropriate to analyze through existing documents and written legal sources. The doubts that arise stem from the mismatch regarding who qualifies as a creator under copyright law with the reality that exists. A creator is an individual or a group of individuals who use human intellectual ability and creativity to produce an original work. Ari Juliano Gema developed a 4-Step Test from the provisions of Article 34 of the Copyright Law. Works entirely produced by Artificial Intelligence cannot meet the requirements for copyright protection, as they lack human personal characteristics. Discussions and considerations by the government need to be carried out to formulate new regulations.